CEO NARCISSISM AND FINANCIAL PERFORMANCE - Fionita, Ita; Susanti, Susanti; Pranyoto, Edi; Lestari, Nyoman (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2024)
Financial performance reflects a company’s operational condition in both favorable and unfavorable periods. Narcissistic CEOs often drive short-term financial gains through risky strategies, but these can result in long-term issues, such as rising debt and declining performance. This study examines the impact of CEO narcissism on financial performance, using Corporate Social Responsibility (CSR) as a mediator. The population consists of state-owned firms in Indonesia, with purposive sampling applied. Data analysis uses the path analysis method. The study finds that CEO narcissism negatively affects both financial performance and CSR. Narcissistic traits, measured through factors like photos and education, harm CSR efforts, though CSR does not mediate the relationship between CEO narcissism and financial performance. The findings suggest that companies should carefully assess narcissistic traits in CEO candidates, as these can harm long-term financial stability and social reputation. Investors are also advised to consider CEO personality traits when making investment decisions.